2003
DOI: 10.1021/ic026219r
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Structural Variety of Diphenyllead(IV) Complexes Obtained by Reaction of Diphenyllead Dichloride with Thiosemicarbazones

Abstract: The reactions of PbPh(2)Cl(2) in methanol with acetophenone, salicylaldehyde, pyridine-2-carbaldehyde, 2-acetylpyridine, and 2-benzoylpyridine thiosemicarbazones (HATSC, HSTSC, HPyTSC, HAcPyTSC, and HBPyTSC, respectively) were explored. Despite the similarities among these ligands, the reactions afforded solids with very diverse compositions and structural characteristics, which were in most cases analyzed by X-ray diffractometry (as was the structure of the free ligand HBPyTSC). In the complexes [PbPh(2)Cl(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 24 publications
10
16
0
Order By: Relevance
“…Namely, the title compound can act as multidentates ligand to bind with one or two or multimetal centers, which allows successful synthesis of homo-and/or heteronuclear metal complexes with interesting stereochemistry. This calculated result not only consists with many experimental facts reported early [28][29][30], but also supports the original idea of our synthesis. On the other hand, comparing the atomic charges of the non-H atoms calculated at B3LYP/ 6-311G * * level in solution-phase with those in gas-phase, it can be found that in solution-phase, the atomic charge values of the S(1) atom and the N(3) atom of C N double bond are bigger than those in gas-phase and their atomic charge values will increase with the increase of the polarity of the solvent.…”
Section: Atomic Charge Distributions In Gas-phase and In Solution-phasesupporting
confidence: 92%
“…Namely, the title compound can act as multidentates ligand to bind with one or two or multimetal centers, which allows successful synthesis of homo-and/or heteronuclear metal complexes with interesting stereochemistry. This calculated result not only consists with many experimental facts reported early [28][29][30], but also supports the original idea of our synthesis. On the other hand, comparing the atomic charges of the non-H atoms calculated at B3LYP/ 6-311G * * level in solution-phase with those in gas-phase, it can be found that in solution-phase, the atomic charge values of the S(1) atom and the N(3) atom of C N double bond are bigger than those in gas-phase and their atomic charge values will increase with the increase of the polarity of the solvent.…”
Section: Atomic Charge Distributions In Gas-phase and In Solution-phasesupporting
confidence: 92%
“…The 1 H, 13 [12] The value of the molar conductivity in DMSO, 8.0 S·cm 2 ·mol -1 (10 -3 ), rules out any ionic behaviour, [23] and is likewise in accordance with the proposed evolution. ,7) are all more shielded than in the free ligand, while C(4,6), C(5) and C(10,11) become deshielded.…”
Section: Solution Studiessupporting
confidence: 70%
“…2-, the Pb(2) atom is octahedrally coordinated. This fragment was previously found in [{PbPh 2 (BPyTSC)} 2 (PbPh 2 Cl 4 )]·2MeOH, [12] although in- (1) and N(7)-H(7A)···Cl(1) (see Table 2). In keeping with this, the Pb(2)-Cl(2) bond in the present compound is shorter than any of the Pb-Cl bonds in the BPyTSC complex, in which both Cl atoms are bridges and one takes part in a hydrogen bond.…”
Section: Solid-state Structuressupporting
confidence: 61%
See 1 more Smart Citation
“…Namely, the title compound can act as multidentate ligand to bind one, two or more metal centers, which could in principle result in the formation of homoand/or heteronuclear metal complexes with interesting stereochemistry. This calculated result is not only consistent with many reported experimental facts [29][30][31], it also supports the original idea of our synthesis. On the other hand, it can be found by comparing the atomic charges of the non-H atoms calculated at B3LYP/6-311G * * level in solution phase with those in gas phase that in solution phase, the atomic charge values of the S(1) atom, the N(1) atom of C=N double bond and N(3) atom are bigger than those in gas phase and their atomic charge values will increase with the increase of polarity of the solvent.…”
Section: Atomic Charge Distributions In Gas Phase and In Solution Phasesupporting
confidence: 93%